Perfil socioeconómico del contribuyente de Guayaquil sujeto al control del servicio de rentas internas en sus obligaciones tributarias - Manya, Marlon (2010)
The following paper presents a statistical model called Logistic Regression to measure the probability of default of different types of taxpayers in the city of Guayaquil when they have to declare their respective tax form, allowing the tax authorities - SRI to take control actions on this non-compliance with tax obligations by establishing the relationship between the explanatory variables and the dependent variable in the model. It also can identify and classify Guayaquil taxpayers who comply with their duties to the Treasury and taxpayers who do not, based on socio-economic variables, coming to define the profiles of the contributors and we can set the gender, age, education level, type of occupation, level of knowledge of tax law, the main reasons that influence when they do not comply their obligations, and measure their level of tax culture of taxpayers.